Exploring The Relationship Between Responsiveness And Usability And Its Impact On Customer Satisfaction In E-Commerce - Fath, Syahrul; Abimanyu, Dimas; Misbak, Misbak (Journal of Management Economic and Financial, 2024)
This research explores the use of chatbots in e-commerce from a customer perspective, with the aim of determining how responsiveness affects usability, as well as how this usability affects customer satisfaction. The data collection method used was a questionnaire distributed to 195 respondents. For model and hypothesis testing, SPSS and AMOS software were used. The results of the validity and reliability tests show that the respondent data is valid and reliable for use in hypothesis testing. The normality test shows that the questionnaire data is normally distributed. The multicollinearity test shows that multicollinearity has occurred. The results of the fit model test are that most of the criteria can be met or are fit, so the statistical interpretation results can not only be used on the sample but on the population as a whole. And the hypothesis test shows that there is a significant positive relationship between responsiveness (X) and usability (Y) of the chatbot. These findings indicate that the more responsive a chatbot is, the higher its level of usefulness in the eyes of customers. When a chatbot is able to provide relevant answers, customers tend to feel that the chatbot is effective and practical to use in meeting customer needs. Furthermore, this research also found that usability (Y) significantly influences customer satisfaction (Z). In other words, easy-to-use and effective chatbots can increase customer satisfaction in an e-commerce context. When a chatbot is designed with a simple interface, customers can easily ask questions and receive the answers or help they need. In addition, if the chatbot is able to provide accurate and relevant answers, customers feel that their needs can be met.